A Simulation Analysis of Tour-Shift Construction Procedures - Mabert, Vincent A.; Watts, Charles A. (Management Science, 1982)
Work force scheduling research over the last few years has concentrated on the shift scheduling problem in service oriented firms (telephone operators, postal employees, bank encoders, etc.). In all cases, the authors were primarily interested in the evaluating procedures (optimal and heuristic) to determine the appropriate number of workers to be assigned to the available set of work schedules to meet fluctuating work volumes. However, more attention should be given to how the available shift schedules were defined (start times, durations, etc.) and their impact on maintaining good productivity levels. This paper analyzes the impact of six different approaches in defining the available weekly tour-shift schedules. Tests are conducted to evaluate the performance of the six approaches using operating data from Ohio National Bank for the check proof and encoding activity. The results of this study provide some useful managerial insights into the issues of effectively staffing personnel on a weekly basis. First, restrictive employment policies/customs can substantially increase costs. Second, structured procedures can be used to identify and build good employment schedules for a weekly assignment. And third, the structured procedures presented here provide useful cost and productivity information for evaluating various staffing decisions, and weighing these decisions with other intangible factors such as employee morale and turnover.